Effectiveness of Online Mediation Application on Divorce Cases Due to Economic Factors - Besse Tenri Abeng Mursyid (Musamus Law Review, 2023)
Data from the Religious Courts Class 1A Palu City reports of lawsuits from January to February 2021 were 289 cases. The Covid-19 pandemic has made the divorce rate increase. The reason is that the causes of divorce during the Covid-19 pandemic, on average, have increased in all regions in Indonesia; it is not the case that divorce is caused by family economic factors that are getting worse. The issuance of the Circular Letter of the Supreme Court Number 1 of 2020 concerning Guidelines for the Implementation of Duties During the Prevention of the Spread of Covid-19 in the Supreme Court and the Judicial Body. One of the implementations of mediation that is often carried out conventionally is now carried out online because of conditions that force the court so that every party seeking justice is still given services, observing the problems faced in mediating as a step to find a solution in a divorce lawsuit at the Religious Court Class 1A City. Palu, this study will examine the rules of the Supreme Court Decision Number 10 of 2016 concerning Mediation Procedures and see Empirical Facts on the Implementation of Online Mediation carried out at the Class 1a Religious Court of Palu City. This study's results indicate that online mediation implementation is still carried out within the stages described in the rules for implementing conventional mediation. However, online mediation brings together the parties that rely heavily on internet connections. As well as related to the effectiveness of its implementation, the authors consider this to be less effective because based on the theory of Legal Effectiveness, it shows one indicator, namely the Legal Factor, in this case, the rules that form the basis for the implementation of mediation are not only guided by the Supreme Court Circular Number 10 of 2016 concerning mediation (conventional) so that law enforcement officers, in this case, the Mediator at the Religious Court Class 1a Palu City are reluctant to carry out Online Mediation. As an implication of this research, it is stated that it is necessary to make laws and regulations that specifically regulate the implementation of mediation both conventionally and online, as well as the need for socialization among parties seeking justice to understand the importance of implementing Online Mediation.